Philanthropy, Integration or Innovation? Exploring the Financial and Societal Outcomes of Different Types of Corporate Responsibility - Halme, Minna (Journal of business ethics, 2009)
This article argues that previous research on the outcomes of corporate responsibility should be refined in two ways. First, although there is abundant research that addresses the link between corporate responsibility (CR) and financial performance, hardly any studies scrutinize whether the type of corporate responsibility makes a difference to this link. Second, while the majority of CR research conducted within business studies concentrates on the financial outcomes for the firm, the societal outcomes of CR are left largely unexplored. To tackle these two deficiencies, this article extends the different conceptualizations of corporate responsibility and elaborates both the financial and the societal outcomes of different types of CR.